2017
DOI: 10.1093/rheumatology/kex258
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of tofacitinib in early arthritis-induced bone loss in an adjuvant-induced arthritis rat model

Abstract: Possible reasons for these observations might be related to the mechanism of action of tofacitinib, which leads to direct interactions with bone metabolism, and/or to the kinetics of its bone effects, which might need longer exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…[ 20 ] JAK inhibition with tofacitinib suppressed the inflammatory response of rats with adjuvant-induced arthritis, illustrating decreased infiltration of synovial sub-lining and lining layers. [ 21 ] Another study showed that increased synovial lining hyperplasia in a rabbit model of chronic antigen induced arthritis was significantly inhibited by tofacitinib. [ 22 ] Changes in musculoskeletal images after treatment with tofacitinib were investigated using ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] JAK inhibition with tofacitinib suppressed the inflammatory response of rats with adjuvant-induced arthritis, illustrating decreased infiltration of synovial sub-lining and lining layers. [ 21 ] Another study showed that increased synovial lining hyperplasia in a rabbit model of chronic antigen induced arthritis was significantly inhibited by tofacitinib. [ 22 ] Changes in musculoskeletal images after treatment with tofacitinib were investigated using ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…The most modern and very promising antirheumatic drugs include the JAK inhibitors. Despite no studies having been published on BMD and JAK inhibition, baricitinib has been shown to suppress osteoclast development by inhibiting expression of RANKL on osteoblasts in vitro, while tofacitinib preserved cortical trabecular hardness in rats [106, 107]. The coming era will reveal whether these drugs will serve as potent osteoprotective agents.…”
Section: Disease-modifying Antirheumatic Drugs (Dmards)mentioning
confidence: 99%
“…We selected adjuvant-induced arthritis (AIA) because it mimics the signs and symptoms of human RA, such as the histopathological changes of inflammation, vascular proliferation, and importantly, the progression to joint destruction [18]. The AIA model has been widely used in the development of antirheumatic drugs, including several non-steroid anti-inflammatories, methotrexate [19], and also biologic drugs, including tocilizumab [20] and Jak-inhibitors like tofacitinib [21].…”
Section: Introductionmentioning
confidence: 99%